Lansky [videorecording (Blu-Ray)] - Keitel, Harvey; Worthington, Sam, 1976-; Robb, AnnaSophia, 1993-; Kelly, Minka, 1980- (Lionsgate, 2021)
When aging gangster Meyer Lansky is investigated one last time by the Feds, who suspect he has stashed away millions of dollars, Lansky spins a dizzying tale, revealing the untold truth about his life as the notorious boss of Murder Inc. and the National Crime Syndicate.